Does Attentional Focus Influence Psychophysiological Responses to an Acute Bout of Exercise? Evidence From an Experimental Study Using a Repeated-Measures Design - Meixner, Friedrich; Herbert, Cornelia (Frontiers in Physiology, 2021)
Attentional focus during aerobic exercise has been studied in the context of sports performance, injury prevention and affective experience. It has been tested if attentional focus influences cardiovascular activity, positive/negative affect, and subjective exertion during a cycling exercise. Data from N=30 female participants has been collected using a repeated measures design, with the following experimental manipulations: A) an internal attention focus (i.e., paying attention to force production of the quadriceps muscles), B) an external attention focus (i.e., paying attention to changes in brightness in the cycling track simulation), and as control conditions C) exercise without attention focus (i.e. no specific instruction was given) and D) no exercise, no attention focus. Subjective affect and exertion were assessed, and changes in cardiovascular activity were recorded via mobile impedance cardiography (ICG) at rest, during and after the exercise, including HR, HRV (RMSSD, HF), PEP, CO, SV, LVET and RSA. Exercise was associated with adaptations in cardiovascular activity, positive/negative affect, and subjective exertion. However, this did not interact with attentional focus. The original hypothesis could not be supported: instructed attentional focus does not influence affect, exertion, or cardiovascular activity during a cycling exercise. Nonetheless, impedance cardiography delivered reliable measurements even during the cycling exercise.